The Many Altars of Modernity: Toward a Paradigm for Religion in a Pluralist Age - Berger, Peter L. (De Gruyter eBook-Paket Theologie, Religionswissenschaften, Judaistik, 2014)
This book is the summation of many decades of work by Peter L. Berger. It outlines a new paradigm for understanding religion and pluralism in an age of multiple modernities. Along the way, Berger addresses a wide range of issues spanning individual faith, interreligious socieities, and the political order. The book also includes responses from three eminent scholars of religion: Nancy Ammerman,Detlef Pollack, and Fenggang Yang